2018
DOI: 10.1016/j.rboe.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral anticoagulants for the prevention of thromboembolic events in the post-operative period of hip arthroplasty: a systematic review

Abstract: Oral anticoagulants are being used in the postoperative period of hip arthroplasty to prevent of thromboembolic events, create doubts as to the effectiveness of thromboprophylaxis and reduce the risk of hemorrhage. This systematic revision is aimed at evaluating the use of oral anticoagulants in the prevention of thromboembolic events in the postoperative period of patients undergoing hip arthroplasty. Research with descriptors found on PubMed, BVS, and the CAPES portal for medical journal publications from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…2 recently published systematic reviews based on clinical trials (Forster and Stewart 2016, Trevisol et al. 2018) both concluded that extended duration thromboprophylaxis should be considered to prevent VTE, when undergoing THA. Forster et al.…”
Section: Discussionmentioning
confidence: 99%
“…2 recently published systematic reviews based on clinical trials (Forster and Stewart 2016, Trevisol et al. 2018) both concluded that extended duration thromboprophylaxis should be considered to prevent VTE, when undergoing THA. Forster et al.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, NOACs (new oral anticoagulants) have been shown to be effective for thromboprophylaxis after total hip arthroplasty (THA) and total knee arthroplasty in randomized controlled trials. Other studies have reported that prophylaxis with RXB for 2 weeks further reduces the risk of VTE following hip or knee arthroplasty14). The use of RXB is safe, without a statistically significant increase in severe hemorrhage or any bleeding15).…”
Section: Discussionmentioning
confidence: 97%